Mastering VMware Infrastructure 3. - McCain, Chris (John Wiley & Sons, 2008)
Mastering VMware Infrastructure 3 offers a strong design component followed by an in-depth look at the day-to-day tasks that make virtualization a key technology for any enterprise. Having access to a massive server infrastructure, the authors are able to provide real-world examples and best practices that apply to the integral parts of the virtual administrator's professional life. Topics include creating and managing virtual networks, creating and managing storage devices, migrating and importing virtual machines, managing and monitoring resource access, and protecting data.